Review of the Youth Subcultures in the Story of Zal and Rodabeh - Mahmood Hokmabadi; AliAsghar Bashiri (Matn/Pizhūhī-i Adabī, 2019)
Subculture, which is part of the culture, on the one hand is in on junction with culture and society and, on the other hand, is in conflict with it in some detail; however, this conflict is not so far to lead to a counter-culture or cultural deviation; but the deviation from the original culture is to get privileges of the community dominant culture sometimes obtained by the bargaining. Youth subcultures are referred to in sociological theories, and many sociologists believe, differences in behavior, dress and even speech and thinking with the general culture and persistence on differences by a large number of young people should be studied as youth subcultures. In Shahnameh by Ferdowsi, in the section on Manuchehr Kingdom, Zal and Roudabeh trying to marry can be seen as the most important youth subcultures in Shahnameh. Both face serious objections to the marriage in society and culture, to which they belong. The current paper investigated how Zal and Roudabeh deal with objections, and how they benefit from the culture of their community from the perspective of subculture theory.